A journal of a voyage of discovery to the Arctic regions, in His Majesty's ships Hecla and Griper, in the years 1819 & 1820 [electronic resource] - Fisher, Alexander, d. 1838. (London : Printed for Longman, Hurst, Rees, Orme, and Brown, 1821)
Tables. Electronic reproduction. Mode of access: Internet. 44